Il sito storico di Virgohamna (Svalbard) e le spedizioni artiche di Andrée e Wellman. Considerazioni a seguito di una ricognizione speditiva con droni - Gianluca Casagrande (Bollettino della Società Geografica Italiana)
The small Danskøya (Danes Island) and Amsterdamøya (Amsterdam Island) are located at the north-western edge of the Svalbard archipelago. Both islands are today completely uninhabited. In 1896 and 1897, Swedish engineer Salomon August Andrée elected the small bay of Virgohamna, on the northern shore of Danskøya, as a starting point for his tragic attempt to reach the North Pole in a balloon. In 1906, 1907 and 1909 the American journalist Walter Wellman, with his airship “America”, tried unsuccessfully to fly to the North Pole. In year 2000, the Norwegian governor of Svalbard (Sysselmannen) regulated access to the historical site, which can now only be visited with prior, special authorization. During summer 2018, the Polarquest2018 Arctic expedition carried out an aerophotographic survey of the area by means of drones. Without the need of landing any crew nor equipment on the beach, two small quadcopters were launched from the support boat and later returned there at the end of their flights. The survey made it possible to acquire an effective “snapshot” of the conservation status of the site more than 121 years after the first historical expedition. Acquired data were processed by an “image-based modelling” software to obtain expeditive ortophotographs and 3-D models. This work presents the research method and may contribute to documenting an important site in the history of Arctic explorations.